O ambiente de controles internos em uma entidade de ensino sob a influência de programas governamentais - Namour, Zaki (2016)
Brazil has witnessed a significant increase of government programs in the last years. They aimed to transform Brazil into a country without poverty, trying to enhance social inclusion and reduce inequality.The National Program for Technical Access Education and Employment (Pronatec), it is the subject of this research. It aims to expand and democratize courses offers for Vocational and Technological Education (EPT) to the Brazilian population, especially to promote the training of young people based on the foregoing throughout a series of programs , projects , technical and financial assistance measures. The courses have been funded by the Federal Government and have been offered free of charge by Institutions of the Federal Vocational Education , Science and Technology ‘s Network, likewise from the State , District and Municipal ‘s networks, vocational and technological education. It is also offer by S Institutions from the S System, including Senac São Paulo, object of this study. Throughout a scholarship “ Bolsa-Formação” Senac São Paulo has received transfers from the National Department due to the execution of hours which requires an internal control in compliance with a proper management, accounting and financial transfers. The aim of this study was to determine whether there were impacts on the management of the internal control at Senac São Paulo for the offer of the Scholarship Exchange Training “ Bolsa-Formacao under the Pronatec and accordingly a case study was conducted. Data collection was done through interviews with managers involved in the operation of Pronatec , reading documents such as management and audit reports. For data analysis, we used the technique of content analysis. The results of this research permitted to make some inferences about the Pronatec offer at Senac São Paulo. There have been changes regarding the internal control practices. The “FIC” and technical courses offers in Senac São Paulo demanded differentiation of internal controls involving mainly the cost of student assistance, inputs required for participation in the courses of the Scholarship Exchange Training and performed hourly load control.